Experimental study on K migration, ash fouling/slagging behaviors and CO2 emission during co-combustion of rice straw and coal gangue. (15th July 2022) - Liu, Lang; Ren, Shan; Yang, Jian; Jiang, Donghai; Guo, Junjiang; Pu, Yubao; Meng, Xianpiao
Abstract: Co-combustion of biomass and coal gangue (CG) is a potential technique for using both resources. The alkali migration plays a key factor for reducing ash slagging and SO2 emission, but its mechanism unclear. Hence, the K migration in co-combustion of rice straw (RS) and CG was well studied in this work. The results indicated that the influence of CG addition on K migration is related to the CG blending ratio. For a CG blending ratio <40%, one hand the released SO2 reacted with KCl and KOH to form relatively stable K2 SO4 ; On the other hand, KCl, KOH and K2 SO4 interacted with mullite and quartz to form KAlSi3 O8 . For a CG blending ratio >40%, K mainly reacted with mullite and quartz to form KAlSi3 O8 . Therefore, co-combustion is expected to reduce SO2 emissions by up to 18.19% at a CG blending ratio of 30%. Furthermore, the ash fouling/slagging tendency decreased from 0.62 without CG to 0.26–0.47 with CG. Considering these reasons, we suggested a 20%–30% CG blending ratio as the optimum feedstock composition for the co-combustion of RS and CG, and the co-combustion could consume 0.17–0.23 kg/(kW·h) of CG and reduce 0.45–0.43 kg-CO2 /(kW·h). Graphical abstract: Image 1 Highlights: The synergistic effect of mullite, quartz and SO2 on K migration was investigated. The effect of K migration on the ash fouling/slagging behaviors was studied. The CO2 emissions during co-combustion of RS and CG were evaluated. The optimum blending ratio of RS and CG for co-combustion was obtained.